Local Transpositions in Alignment of Polyphonic Musical Sequences - Allali, Julien; Ferraro, Pascal; Hanna, Pierre; Iliopoulos, Costas (String Processing and Information Retrieval, 2007)
Music retrieval systems based on melodic similarity consider sequences of notes. Adaptations of edit-based algorithms, mainly applied in bioinformatic applications, to the musical domain lead to promising results. However, new problems are raised when considering polyphonic music. Existing representations of notes do not allow retrieval systems to be transposition invariant. In this article, we propose a new dynamic programming algorithm that permits to take into account multiple local transpositions. Experiments with MIREX collections have been performed to evaluate the improvements induced by this algorithm. The results clearly show the contribution of this algorithm: it is confirmed as the most accurate solution for a music retrieval system based on alignment algorithm to be transposition invariant.